Flagged License Plate Detection And Warning (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
CCTV Camera nowadays captures high-resolution video which can be used to analyse frames to fetch text by using the technique of Optical Character Recognition (OCR). FLPDW (Flagged License Plate Detection and Warning) uses Deep Neural Networks (DNN) techniques to isolate number plates from a given frame and fetch License Plate Number as plain text and compare it with predefined suspicious database and give a warning to authorities when a Suspicious License Plate (SLP) is found.